Performance, emissions and lubricant oil analysis of diesel engine running on emulsion fuel. (1st June 2016) - Hasannuddin, A.K.; Wira, J.Y.; Sarah, S.; Wan Syaidatul Aqma, W.M.N.; Abdul Hadi, A.R.; Hirofumi, N.; Aizam, S.A.; Aiman, M.A.B.; Watanabe, S.; Ahmad, M.I.; Azrin, M.A.
Highlights: The rate of NOx and PM reduction was lower than the rate of CO increase when using emulsion fuel. The lubricant oil viscosity variation did not exceed the limits during the engine operation. Emulsion fuel offers beneficial properties in terms of lower wear and friction. Average depletions of lubricant oil additives were found at the lowest level for emulsion fuel in compared with D2. Abstract: Emulsion fuel is one of the alternative fuels for diesel engines which are well-known for simultaneous reduction of Particulate Matter (PM) and Nitrogen Oxides (NOx ) emissions. However lack of studies have been conducted to investigate the effect of emulsion fuel usage for long run. Therefore, this study aims to investigate the effect of lubricant oil in diesel engine that operated using emulsion fuels for 200 h in comparison with Malaysian conventional diesel fuel (D2). Two emulsion fuels were used in the experiment comprising of water, low grade diesel fuel and surfactant; with ratio of 10:89:1 v/v% (E10) and 20:79:1 v/v% (E20). Engine tests were focused on fuel consumption, NOx, PM, Carbon Monoxide (CO), Carbon Dioxide (CO2 ), Oxygen (O2 ) and exhaust temperature. Parameters for the lubricant oil analysis measured were included kinematic viscosity, Total Acid Number (TAN), ash, water content, flash point, soot, wear metals and additive elements. The findings showed the fuel consumption were up to 33.33% (including water) and lower 9.57% (without water) using emulsion. The NOx and PM were reduced by 51% and 14% respectively by using emulsion fuel. Kinematic viscosity, TAN, ash, water content, flash point and soot for emulsion fuel were observed to be better or no changes in comparison to D2. The emulsion fuel did not cause any excessive amount of metals or degraded the additive. The average percentage of wear debris concentration reduction by emulsion fuel were 8.2%, 9.1%, 16.3% and 21.0% for Iron (Fe) Aluminum (Al), Copper (Cu) and Lead (Pb) as compared to D2 respectively.